Formation of Adaptive and Integrative Potential of Children with Mental Retardation in Artistic and Creative Activities - O. A. Denisova; T. V. Gudina; I. A. Bukina; O. L. Lekhanova; A. V. Selina (Образование и наука, 2019)
Introduction. Over the past decades, Russian society has seen an increase in humanistic trends related to a more attentive and more careful attitude towards the qualitative diversity of society than before. In particular, there are significant changes in the education and upbringing of children with mental development problems (deviations or disorders). Creating the conditions for the full and dignified existence of such children is impossible without their inclusion in social relations, without the support of the process of formation of their individuality, which is particularly significant at the early stages of ontogenesis, when the foundations are laid down and cultural and social norms of behaviour are learned.The aims of the present publication are the following: to describe diagnostic tools for identifying the level of formation of the adaptation and integration potential of children with mental retardation of primary school age; to demonstrate the ways of this potential development by means of artistic and creative activities.Methodology and research methods. The research was based on the principles of individualisation and differentiation of correctional and pedagogical process; the capacities, characteristics of development and needs of each child; systemacity of training with close cooperation of all its participants; compliance of requirements, methods, techniques and educational conditions with individual and age characteristics of students. In the course of the experiment, a complex of diagnostic and correctional-developing methods was used: “Finish the Story” (G. A. Uruntayeva, Yu. A. Afon’kin), “Story Pictures” (R. R. Kinina), “Rukavichki” (G. A. Zuckermann), etc. The obtained data were processed through a mathematical method of assessing the significance of differences using the Spearman’s rank correlation coefficient.Results and scientific novelty. The research presents the developed and tested methodology of diagnostics of adaptive and integrative potential of children of primary school age with mental retardation. This methodology was developed in educational establishments, including children’s art schools. The criteria and qualitative characteristics of the levels of formation of this potential are highlighted. Three of its structural components – cognitive, emotional and behavioural – are identified, which are proposed to be developed through artistic and creative activities with close cooperation of specialists of the school support service, parents and teachers of additional education. Such activities are considered as a specially organised process with personal-oriented goals, in which art acts as a determinant of the socio-cultural formation of a child’s personality and contributes to his or her successful inclusion in the school community of peers and further socialisation. The idea and concept of improving correctional and pedagogical work with children with special educational needs through artistic creativity are based on: the predisposition of any child to it, regardless of the presence/absence of any nosology; the accessibility for everyone of this way of learning the world around.Practical significance. The research materials can be used in the practice of special psychologists, rehabilitators, defectologists, teachers of children additional education, as well as in the system of training, advanced training and retraining of pedagogical personnel.